2006
DOI: 10.1097/01.yic.0000194377.88330.1d
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized, parallel-group, flexible-dose study to evaluate the tolerability, efficacy and effects of treatment discontinuation with escitalopram and paroxetine in patients with major depressive disorder

Abstract: This multinational, randomized, double-blind, flexible-dose study evaluated the short- and long-term antidepressant tolerability and efficacy of escitalopram and paroxetine. Tolerability was assessed by monitoring adverse events throughout the study, and discontinuation events during brief treatment interruption and tapered withdrawal. Discontinuation-emergent effects were evaluated in two separate double-blind periods. First, to mimic the consequences of non-compliance, patients were randomized to one of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 26 publications
5
97
0
Order By: Relevance
“…Baldwin et al [45] evaluated the difference between abrupt and tapered discontinuation when using paroxetine or escitalopram in patients with MDD. Discontinuation-emergent effects were assessed in two separate double-blind periods.…”
Section: Resultsmentioning
confidence: 99%
“…Baldwin et al [45] evaluated the difference between abrupt and tapered discontinuation when using paroxetine or escitalopram in patients with MDD. Discontinuation-emergent effects were assessed in two separate double-blind periods.…”
Section: Resultsmentioning
confidence: 99%
“…Antidepressants were the most frequently dispensed prescription drugs in the United States (US) in 2011 accounting for $11 billion in sales and 264 million prescriptions filled [2]. Sexual dysfunction, which can involve any or all phases of the sexual response cycle (i.e., libido, arousal, orgasm and ejaculation), is associated with both the condition and the treatments used, can affect up to 50 percent of untreated depressed patients [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, escitalopram was significantly more effective in 3 studies [18][19][20] while no significant difference was found in 2 studies [21,22]. Two of the 3 studies comparing escitalopram with paroxetine showed the superiority of escitalopram with respect to both safety and efficacy [3,23,24]. All other RCTs found no significant differences in safety or efficacy between SSRIs: escitalopram and fluoxetine [25,26]; citalopram and sertraline [27]; fluoxetine and sertraline [28]; fluoxetine, sertraline and paroxetine [29] and fluvoxamine, sertraline and paroxetine [30].…”
Section: Introductionmentioning
confidence: 88%
“…MDD is a serious psychiatric condition with a significant impact on public health. The medical burden of this pathology is tremendous: 70% of suicides are committed by depressed individuals, not treated nor diagnosed [3,4]. In this context, the efficacy and safety of medical treatments are essential.…”
Section: Introductionmentioning
confidence: 99%